An Overview on Dizziness: Medical Therapy and Diagnosis - Acharya, Debashis (Research Developments in Medicine and Medical Science Vol. 2, 2023)
The key concepts in assessing, diagnosing and managing common vestibular disorders are briefly described. Differential diagnosis of vertigo along with certain characteristic traits are mentioned. Etiology and pathophysiology of associated symptoms of dizziness are discussed. The article gives a general overview of vertigo and how to treat it. Both researchers studying vertigo and doctors who treat vertigo can benefit from it. It introduces medical professionals to a methodical method of evaluating patients who are dizzy. It takes a lot of practise to master Verigo. A solid history is first and foremost the cornerstone of treating a patient who is dizzy. This is followed by appropriate examination and investigations. The general practitioner is the first expert to be involved in the management of dizzy patient followed by specialists in particular Otorhinolaryngologists, Audiovestibular Medicine Specialists and Neurologists and finally, allied healthcare personnel. Here are a few succinct descriptions of the key ideas in assessing, diagnosing, and treating common vestibular disorders. Vertigo differential diagnosis and a few identifying characteristics are mentioned. The pathophysiology and aetiology of the associated symptoms of lightheadedness are discussed. Timing and triggering factors' importance is emphasised. The role of nystagmus in separating central from peripheral vertigo is discussed along with balance and gait. Drug therapy and physical rehabilitation reduce the functional disability of vertigo patients & improve their quality of life.